'It's a double whammy': A qualitative study of illness uncertainty in individuals with Parkinson's disease in the context of COVID-19. (December 2022) - Simpson, Jane; Zarotti, Nicolò; Varey, Sandra; Anestis, Eleftherios; Holland, Carol; Murray, Craig; Eccles, Fiona JR
Objectives: The purpose of this study was to explore the experiences of individuals with Parkinson's through the theoretical lens of illness uncertainty during the first UK full lockdown period (March–June 2020) put in place due outbreak of the COVID-19 pandemic. Methods: Individual semi-structured interviews were carried out via telephone in May 2020 with 10 individuals with Parkinson's (six men and four women) recruited from Parkinson's UK. Interviews were recorded and transcribed verbatim, and thematic analysis was adopted to analyse the resulting data. Results: Four overarching themes emerged from the interview data: (1) COVID-19 amplifying existing fears and difficulties around the uncertainty of Parkinson's; (2) practical and psychological efforts to manage uncertainty; (3) benefit-finding as a way of acknowledging the positives of lockdown; (4) risk and future management in the context of uncertainty. Discussion: Participants reported a range of implicit and explicit strategies to cope with the 'double whammy' of uncertainty caused by having Parkinson's during a global pandemic. While these were generally successful in maintaining well-being, it is important that such successful accounts are used to help inform novel strategies and interventions targeting individuals who might need additional support.